Quantitative Analysis of Frozen Section Histology in Mohs Micrographic Surgery. Issue 7 (July 2020) - LeBoeuf, Matthew; Bieber, Karen; Cooper, Sherrie; Isenor, Amanda
Abstract : BACKGROUND: Mohs micrographic surgery (MMS) relies on complete frozen tissue sections for the unique combination of high cure rates and tissue preservation. OBJECTIVE: To quantify and characterize the tissue sectioning process in MMS. MATERIALS AND METHODS: Two hundred eighty-four tissue blocks were analyzed. The histotechnician measured the depth cut into the tissue block for every section placed on the slide. The surgeon identified complete sections. RESULTS: First-stage complete sections were achieved at 285 μm. The ear and hair-bearing cheek required increased depth of sectioning compared with other sites. Small pieces of tissue achieved complete sections at a decreased depth compared with medium or large pieces of tissue. The methodology used in this study was able to identify statistically significant differences between histotechnicians. CONCLUSION: More than 2, 000 measurements on 284 tissue blocks provided quantitative data of the tissue sectioning process in MMS, confirming that MMS allows evaluation of both peripheral and deep margins within hundreds of microns of the margin. Results from this study indicate a methodology that is easily implemented providing interpretable data that can be used to assess and improve tissue sectioning ensuring MMS remains the gold standard for removal of challenging cutaneous tumors.